The protective role of vitamin C in the management of COVID-19: A Review - Mohammad Sarowar Uddin; Md. Shalahuddin Millat; Prodip Kumar Baral; Mahmuda Ferdous; Md. Giash Uddin; Md. Shahid Sarwar; Mohammad Safiqul Islam (SpringerOpen, 2021)
Abstract Background The outbreak of coronavirus infectious disease-2019 (COVID-19) is globally deemed a significant threat to human life. Researchers are searching for prevention strategies, mitigation interventions, and potential therapeutics that may reduce the infection's severity. One such means that is highly being talked in online and in social media is vitamin C. Main text Vitamin C is a robust antioxidant that boosts the immune system of the human body. It helps in normal neutrophil function, scavenging of oxidative species, regeneration of vitamin E, modulation of signaling pathways, activation of pro-inflammatory transcription factors, activation of the signaling cascade, regulation of inflammatory mediators, and phagocytosis and increases neutrophil motility to the site of infection. All of these immunological functions are required for the prevention of COVID-19 infection. Conclusion Considering the role of vitamin C, it would be imperative to administrate vitamin C for the management of severe COVID-19. However, there is no specific clinical data available to confirm the use of vitamin C in the current pandemic.